Desenvolvimento de órtese dinâmica para membro inferior de pessoas com hemiplegia : um protótipo de inovação tecnológica - Ferreira, Luana de Lima (2024)
Introduction: Gait performance is often compromised after post-stroke spasticity. The use of orthoses reduces kinesiological problems of the ankle-foot complex and improves spatial-temporal gait performance. Objective: To develop a prototype of ankle-foot orthosis to facilitate the gait of individuals with hemiplegia. Method: Descriptive applied/technological and experimental study. The assembly was designed with the aid of BLENDER® software. Printing was carried out at the FabLab - UFPB, using Acrylonitrile Butadiene Styrene (ABS) polymer as the material of choice. The production process of shape memory alloy (SMA) was carried out through stages such as casting and machining of the alloy. The test was conducted with test specimens of ABS material and SMA, using equipment from Shimadzu Brazil. Results: The prototype was printed using a nozzle temperature of 250ºC and a bed temperature of 100ºC. The printing time for the parts was 17 hours and 32 minutes. 155.12g and 52.01m of ABS material were used. Flexion tests showed that the ABS material followed a linear behavior up to 1.09mm and tended to increase, favoring an elastic behavior for ABS. For SMA, a similar behavior was observed for the two tested specimens, with no rupture during the test. Conclusion: 3D-printed orthoses can be applied to produce customized products quickly and at a lower cost by promoting limitation to plantar flexion movement and producing a physiological gait pattern during gait phases.